PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT.RADITYA DEWATA PERKASA CABANG GIANYAR - Anak Agung Intan; Nengah Landra; Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Employee performance is an important thing for an organization because good employee performance will affect the progress or survival of an organization in achieving goals. The existing human resources in the company must be utilized as well as possible so that they are able to provide maximum results for the company and can improve the quality of human resources, namely by making every employee have good and quality performance. This study aims to determine the effect of leadership style, work environment and work culture on the performance of employees of PT. Raditya Dewata Enriches Gianyar Branch. The location of this research was conducted at PT. Raditya Dewata Enriches Gianyar Branch. This research is a quantitative research using primary data sources. Primary data used in the form of distributing questionnaires as many as 32 employees at PT. Raditya Dewata Enriches Gianyar Branch. The sampling technique in this research is saturated sampling. The data analysis technique used multiple linear regression analysis. The results showed that the influence of leadership style, work environment and organizational culture had a positive effect on employee performance at PT. Raditya Dewata Enriches Gianyar Branch. The suggestions that can be given to further researchers who conduct similar research can use or add other independent variables and further researchers are advised to expand the object of research.